Integrated Curriculum Management in Religious and Science Education at Madrasah Aliyah - Nenda Nenda; Armai Arif; Widia Winata (PT. Publikasiku Academic Solution, 2025)
This research focuses on integrated curriculum management at Madrasah Aliyah (MA) Al Baqiyatusholihat Bekasi, with the aim of overcoming the gap between religious and science education. This research aims to analyze the process of planning, organizing, implementing, and evaluating the integrated curriculum at MA Al Baqiyatusholihat, as well as identifying effective curriculum integration models between religious and science education. This research uses a descriptive qualitative approach with data collection methods through interviews, documentation, and observation. The resource persons consisted of the head of madrasah, deputy head of madrasah, teachers, and students. The results showed that integrated curriculum management at MA Al Baqiyatusholihat involves planning which includes integration of curriculum objectives and content, organization of intracurricular and extracurricular curriculum, and implementation which involves religious habituation. Curriculum evaluation is carried out using the CIPP (context-input-process-product) model. The curriculum integration model implemented at MA Al Baqiyatusholihat shows effectiveness in creating knowledgeable and moral students. However, there are still challenges in implementation that need to be overcome to achieve more holistic educational goals. This research contributes significantly to the development of an integrated curriculum model that can be adopted by other madrasahs, and recommends the need for a more systematic approach to curriculum management to improve the relevance of education in Indonesia.